KONTRIBUSI DAYA LEDAK OTOT TUNGKAI TERHADAP KETERAMPILAN TENDANGAN KE GAWANG PEMAIN SEPAKBOLA - Muh. Syarif R; Wahyudin Wahyudin; Sulaeman Sulaeman (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
This study aims to determine the level of leg muscle power, the level of ability to kick on goal and the contribution of leg muscle power to the ability to kick on goal for the Sport Science Fc Team Players. This type of research is a type of quantitative descriptive research. The number of samples in this study were 30 people who were selected through the total sampling technique. The data collection technique used a leg muscle power test (vertical jump test) and a kick to goal test. The results of the analysis show that the level of leg muscle power of the Sport Science Team Players is in the medium category and the level of ability to kick on goal is in the medium category. The results of the regression test showed a significant value of 0.008 < P 0.05. This means that there is a significant contribution of leg muscle power to the ability to kick on goal for the Sport Science Fc Team Players. Furthermore, the value of R Square is known to be 0.229. This means that leg muscle power contributes 22.9 percent to the ability to kick on goal in Sport Science Fc Team Players.